The relationship between the geohydrological, geophysical and physical parameters of the Vaalharts aquifer - Oberholzer, Schalk J. (University of the Free State, 2018)
As with any human intervention, the balances of nature are impacted when applying irrigation water. The biggest changes usually manifest as a rise in the groundwater level, as well as a build-up of salts in the soils and groundwater. The impact of irrigation on the natural balances, however, can be controlled to a certain extent through farming and irrigation practices, and scientific methods for fast and efficient monitoring are continually evolving. In the Vaalharts Irrigation Scheme, a very shallow water level (+/- 2 m) of the underlying aquifer, interacts with the irrigated soil zone. Because of this interaction, the build-up of the salt load in the deeper aquifer cannot be ruled out. This may have a direct impact on the cultivation of perennial crops, especially pecan nuts, which are not very salt tolerant. With a shortage of irrigation water in times of drought and with climate change a very real scenario, farmers are starting to exploit groundwater to augment surface water. Unfortunately, the groundwater is much more saline than the surface water due to the local geology that constitutes the aquifer adding to the problem of salinization. In the short-term, exploitation of the Vaalharts Aquifer may provide a solution, but eventually it must impact on the broader hydrological system as it has a direct influence on the environmental balances that currently exist. Thus, the aims and objectives of this study was to apply electrical geophysical methods to determine the lateral and vertical extent of the Vaalharts Aquifer, to determine any lateral homogeneity/inhomogeneity in the underlying geology and to investigate the relationship between the geohydrological, geophysical- and physical parameters of the aquifer. Field investigations included pumping testing and VES soundings at locations of known geology and the measuring of the electrical conductivity of groundwater samples. An ERT traverse provided insights to the lateral variation in geology. Inverse modelling of the electrical data was constrained to the geological layers and the layer resistivities determined. The Dar Zarrouk parameters were correlated with known hydrological parameters (T and K) to establish a relationship. A linear relationship was found between transmissivity (T) and longitudinal conductance (C) with the determination of the factor of proportionality (β). This factor was used to calculate T and K values at VES stations where no geohydrological data were available. Although the data points were few and far between, the calculated data enabled the compilation of contour maps that gives an indication of the lateral distribution of the hydrological parameters in the Vaalharts area. This project thus established a method for use in evaluating the aquifer for groundwater exploitation, that may be extended to the monitoring of salinization in the aquifer.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2018
Keywords: Groundwater -- South Africa -- Vaalharts; Aquifers; Irrigation water; Irrigation -- South Africa -- Vaalharts